THE INFLUENCE OF INSTAGRAM INFORMATION QUALITY ON BKKBN'S IMAGE: CASE STUDY ON EARLY MARRIAGE CONTENT ON @BKKBNOFFICIAL INSTAGRAM ACCOUNT - Wahyutomo, Ryan Tejo; Delliana, Santi (Universitas Swadaya Gunung Jati, 2024)
The BKKBN is one of the institutions that actively provides educational opportunities through Instagram. This research aimed to establish whether the level of the information supplied on Instagram by @bkkbnofficial impacted the public's perception of BKKBN and how much of an impact that information had. The theory that is utilized is the theory of agenda setting. This study applies a quantitative methodology, and the data collection is accomplished utilizing a survey. The sampling of 400 respondents using the simple random sampling method indicates that population members are selected following specific considerations and by distributing questionnaires through Google Forms. The ideas of Information and Image Quality were utilized in the process of carrying out this research. According to the findings of this investigation, the standard of information provided on Instagram by BKKBN's official account influences the brand's public perception. While the effect of the quality of information posted on Instagram by BKKBN Official (@bkkbnofficial) has a 61.1% influence on the image of BKKBN, the impact of other elements that were not included in this study can be much more significant.